IMPROVING UNDERSTANDING OF THE CONCEPT OF ADDITION AND SUBTRACTION THROUGH THE APPLICATION OF PANJURANG MEDIA IN GRADE II STUDENTS: Makasar, Indonesia - Hasanah, Nurul; Rahmawati Patta; Andi Dewi Riang Tati (Jurnal Math-UMB.EDU, 2025)
This research is motivated by the low understanding of mathematics concepts of grade II students in addition and subtraction of integers, as well as the lack of student involvement in the learning process. This research aims to improve the understanding of mathematical concepts through the application of Panjurang (Addition and Subtraction Board) media. The type of research used is Class Action Research (CAR) which is carried out in two cycles, each consisting of the planning, action implementation, observation, and reflection stages. The subjects of the study were 20 students of grade II UPT SPF SD Inpres Ikip Campus. Measurement of concept comprehension refers to the classic Bloom Taxonomy of Comprehension (C2) level, which includes translation, interpretation, and extrapolation abilities because all three aspects are relevant to assessing students' understanding of symbols, meanings, and patterns in computational operations. In Cycle I, the results of observations showed that the learning process from both the teacher and student side and the learning outcomes were still in the category of adequate. After improvements were made in Cycle II, there was a significant improvement in all aspects, namely the learning process from the teacher's side, the learning process from the student side, and learning outcomes, increasing to the good category. This increase is characterized by more active student involvement, more optimal use of Panjurang media, and increased student learning completeness. Thus, it can be concluded that the use of Panjurang media is effective in improving the understanding of mathematics concepts of grade II students in addition and subtraction materials. Keywords: Media Barriers, Conceptual Understanding, Classroom Action Research, Bloom's Taxonomy, Mathematic In Primary School